Clinical outcomes following isolated transcatheter tricuspid valve repair: a meta-analysis and meta-regression study. (14th October 2021) - Bocchino, P P; Angelini, F; Vairo, A; Andreis, A; Fortuni, F; Franchin, L; Frea, S; Raineri, C; Pidello, S; Conrotto, F; Montefusco, A; Alunni, G; et al.
Abstract: Background: Significant tricuspid regurgitation (TR) is a common valvular heart disease worldwide. Purpose: We aimed to assess the pooled clinical and echocardiographic outcomes of different isolated transcatheter tricuspid valve repair (ITTVR) strategies for significant (≥ moderate) TR. Methods: We systematically searched the literature for studies evaluating the efficacy and safety of ITTVR for significant TR in adult. The primary outcomes were the improvement of New York Heart Association (NYHA) functional class and 6-minutes walking distance (6MWD) and the presence of severe or greater TR at the last available follow-up of each individual study. Random-effect meta-analysis was performed comparing outcomes before and after ITTVR. Results: 14 studies with 771 patients were included. Mean age was 77±8 years and mean EuroScore II was 6.8%±5.4%. At a weighted mean follow-up of 212 days, 209 (35%) patients had a NYHA III to IV functional class compared to 586 (84%) patients at baseline (risk ratio: 0.23, 95% CI 0.13 to 0.40, P-value<0.001). 6MWD significantly improved from 237±113 meters to 294±105 meters (mean difference: +50 meters, 95% CI +34 to +66 meters, P-value<0.001). 147 (24%) patients showed severe or greater TR after ITTVR compared to 616 (96%) at baseline (risk ratio: 0.29, 95% CI 0.20 to 0.42, P-value<0.001). Conclusion: Patients undergoing ITTVR for significant TR experienced a significant improvement in NYHA functional status and 6MWD and a significant reduction in TR severity at mid-term follow-up. Funding Acknowledgement: Type of funding sources: None.